Synthesis of an in situ core–shell interlink ultrathin-nanosheet Fe@FexNiO/Ni@NiyCoP nanohybrid by scalable layer-to-layer assembly strategy as an ultra-highly efficient bifunctional electrocatalyst for alkaline/neutral water reduction/oxidation. Issue 9 (10th February 2021) - Che, Qijun; Zhou, Xingyu; Liu, Quancen; Tan, Ya; Li, Qing
Abstract : Self-standing in situ core–shell interlink ultrathin-nanosheet Fe@Fe x NiO/Ni@Ni y CoP nanohybrid was prepared by the fast two-step electrodeposition pathway as a low-cost, ultra-highly efficient and stable true bifunctional electrocatalyst for water reduction/oxidation. Abstract : One of the tremendous challenges for industrially profitable water electrolysis by a more economically viable electrochemical approach is to exploit earth-abundant and ultra-efficient bifunctional (pre)electrocatalysts. Herein, a scalable layer-to-layer assembly strategy is first proposed to delicately construct in situ core–shell Fe@Fe x NiO nanosphere interlink ultrathin Ni@Ni y CoP nanosheet nanohybrids on Ni-foam via controllable two-step electrodeposition pathway. By deliberately introducing metallic Fe and Ni into amorphous Fe x NiO/Ni y CoP nanoclusters serving as the everlasting-conductivity and attached-active-sites along with morphological controls, Fe@Fe x NiO/Ni@Ni y CoP nanohybrids achieved ultralow overpotentials of 92 and 270 mV at 100 mA cm −2 for the electrocatalytic hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) with uncompromising long-term durability for 100 h in 1 M KOH alkaline-electrolyte, respectively, and was even superior to the Pt plate and RuO2 at larger current density ( η OER = 400 mV, η HER = 129 mV at 1500 mA cm −2 ). Besides, it also exhibited wonderful catalytic activity in 1 M phosphate-buffer-solution (PBS, pH = 7), achieving a cell-voltage of 1.86 V at 10 mA cm −2 . The metallic Ni bonding amorphous Ni y CoP was recognized as high-intrinsic HER activity, whereas the Fe@Fe x NiO coupling in situ newly generated NiCoOOH species on the Ni@Ni y CoP surface-layer was identified as intrinsic OER active-matter. Synergistic effects between Fe@Fe x NiO and Ni@Ni y CoP further accelerated the water-splitting dynamics. Impressively, the bifunctional Fe@Fe x NiO/Ni@Ni y CoP/NF achieves an alkaline cell-voltage of 1.43 V at 10 mA cm −2, representing the best bifunctional material hitherto, which is promising for the scale-up commercialization of the production.